2015
DOI: 10.1109/jbhi.2015.2404829
|View full text |Cite
|
Sign up to set email alerts
|

Predicting Asthma-Related Emergency Department Visits Using Big Data

Abstract: Asthma is one of the most prevalent and costly chronic conditions in the United States, which cannot be cured. However, accurate and timely surveillance data could allow for timely and targeted interventions at the community or individual level. Current national asthma disease surveillance systems can have data availability lags of up to two weeks. Rapid progress has been made in gathering nontraditional, digital information to perform disease surveillance. We introduce a novel method of using multiple data so… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
75
0
3

Year Published

2016
2016
2021
2021

Publication Types

Select...
4
3
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 158 publications
(80 citation statements)
references
References 17 publications
2
75
0
3
Order By: Relevance
“…Early detection of disease outbreaks is not a new issue but it remains crucial. In 2015, still many researchers [8] [9][10] tried to develop the ultimate surveillance system using search engines, social network, or wiki data. While authors combined more and more data sources for their surveillance systems, the use of health system data remained limited.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Early detection of disease outbreaks is not a new issue but it remains crucial. In 2015, still many researchers [8] [9][10] tried to develop the ultimate surveillance system using search engines, social network, or wiki data. While authors combined more and more data sources for their surveillance systems, the use of health system data remained limited.…”
Section: Discussionmentioning
confidence: 99%
“…Ram et al [8] aggregated data from Google and Twitter with air pollution data to predict asthma-related ED visits. Unlike Hu et al [5], the researchers had to be satisfied with data from one hospital.…”
Section: Discussionmentioning
confidence: 99%
“…Prior literature has consistently suggested that approximately 1% of tweets are geotagged, thus providing the data on latitude and longitude of the locations where the tweets are posted (e.g., Jahanbakhsh & Moon, 2014;Mislove, Lehmann, Ahn, Onnela, & Rosenquist, 2012;Ram et al, 2015;Young, Rivers, & Lewis, 2014). In addition, around 70% of Twitter users self-report their geographic locations on their Twitter profiles (e.g., Mislove et al, 2012;.…”
Section: Sentiment Analysismentioning
confidence: 99%
“…In addition, social media data have been used to improve our understanding of Ebola [12] and Zika virus infections [13][14][15]. While disease surveillance efforts tend to focus on acute infectious diseases, studies have also been conducted on chronic diseases such as cancer [16], hypertension [16], asthma [16][17][18], diabetes [19], and seasonal allergic rhinitis (SAR) [20][21][22]. Systematic reviews have also been conducted on disease surveillance based on social media data [23][24][25].…”
Section: Introductionmentioning
confidence: 99%